2015
DOI: 10.1007/s13197-015-1849-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying methods on rheological and textural properties, and color changes of wild sage seed gum

Abstract: The effect of different drying methods, oven drying (40-80°C), freeze drying (−40°C) and vacuum oven drying (100 mbar, 50°C) on the rheological and textural properties, and color changes of wild sage seed gum were investigated in this study. The results showed that the apparent viscosity of gum solution (0.6 % w/w), was varied from 0.162 to 0.344 Pa×s (60 s −1 ), and freeze-dried gum exhibited the highest viscosity value among all dried gums. Standard error (SE) and correlation coefficient (R) methods were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 25 publications
5
17
0
Order By: Relevance
“…Non-Newtonian shear-thinning behavior from the flow curves sunflower seed cake (pretreated and non-treated) exhibit is observed. A similar shear-thinning behavior has also been observed for sesame seed [23] and sage seed solutions [24].…”
Section: Rheological Properties Of Sunflower Seed Mesh After Ped Treasupporting
confidence: 77%
“…Non-Newtonian shear-thinning behavior from the flow curves sunflower seed cake (pretreated and non-treated) exhibit is observed. A similar shear-thinning behavior has also been observed for sesame seed [23] and sage seed solutions [24].…”
Section: Rheological Properties Of Sunflower Seed Mesh After Ped Treasupporting
confidence: 77%
“…As the computer vision system perceived color as RGB signals, which is device‐dependent, the taken images were converted into L * a * b * units to ensure color reproducibility. In the L * a * b * space, the color perception is uniform, and therefore, the difference between two colors corresponds approximately to the color difference perceived by the human eye (Salehi and Kashaninejad ). L * (lightness/darkness that ranges from 0 to 100), a *(redness/greenness that ranges from −120 to 120) and b * (yellowness/blueness that ranges from −120 to 120) were measured (Salehi and Kashaninejad ).…”
Section: Methodsmentioning
confidence: 99%
“…Table 3 shows 15 of 46 variables relating to color space models where the lowest rank occurred. Analysis showed that the 5 lowest variables occurred in respect of the following variables: CB_MEAN-specifying the average for component difference of the illumination and the color blue in YCbCr model, HSV_HUE-defining the average component of hue, which had a value ranging 0 7 360 in HSV model (Salehi and Kashaninejad 2015), CR_MEDIAN-defining the median of the component difference of the illumination and the color red, G_STD and G_MEAN-determining the standard deviation and the average components of green color RGB model (Table 3). The highest rank of variable occurred in respect of the following variable: Y_MAXspecifying the maximum for component of the light intensity (luminance) in YCbCr model (Table 3).…”
Section: Results Of Analysis Of Sensitivity To Input Variablesmentioning
confidence: 99%